Omega-6: its pharmacology, effect on the broiler production, and health - Nur Mahendra, Mohamad Yusril; Kamaludeen, Juriah; Pertiwi, Herinda (Hindawi Limited, 2023)
Lipids and oils are the primary sources of monounsaturated and polyunsaturated fatty acids (MUFA and PUFA), which are necessary for human and animal health. Omega-3 and omega-6 are essential nutrients for broilers. Omega-6 members, such as linolenic acid, are essential for broilers and must be obtained through feed. Vegetable oils are the primary source of omega-6 added to broiler feeds. Unsaturated fatty acids are better digested and absorbed than saturated fatty acids and generate more energy at a lower cost, boosting productivity. Feeding supplements with omega-6 can increase the fatty acid content in meat and increase weight, carcass, viscera, and FCR. The quality of meat taste and antioxidant content was also improved after giving omega-6 and influencing mineral metabolism. Broiler reproductive performance is also enhanced by reducing late embryonic mortality, hence enhancing fertility, hatchability, sperm quality, and sperm quantity. Meanwhile, for broiler health, omega-6 can lower cholesterol levels, triglycerides, very low-density lipoprotein, and low-density lipoprotein. It also supports support for T-helper cell (TH)-2-like IgG titers, increasing prostaglandins, eicosanoids, and antioxidants. In addition, it also supports anti-inflammation. Other researchers have extensively researched and reviewed studies on the effects of omega-6 on poultry. Meanwhile, in this review, we provide new findings to complement previous studies. However, further studies regarding the effects of omega-6 on other poultry are needed to determine the performance of omega-6 more broadly.